THE IMPACT OF COVID-19 PANDEMIC ON THE ISLAMIC BANK FUND-RISING PERFORMANCE (Case Study at PT Bank Syariah Bukopin Tbk.) - Windawati, Atif; Widodo, Saniman; Widowati, Mustika; Widodo, Sartono; Katrina Sari, Mella (International Journal of Economics, Business and Accounting Research (IJEBAR), 2025)
The financial performance of Islamic Banks during the Covid-19 pandemic is interesting and important to study because of its function as an intermediary institution. The research has a purpose to investigate the fund-raising performance in Islamic Bank before and during the Covid-19 pandemic. The object of this study is Bank Syariah Bukopin in Indonesia. The different tests namely The Paired Sample t-test and the Wilcoxon Signed Rank Test are used to find out the distinction of Islamic Bank’s fundraising performance before and during the Covid-19 pandemic. As the result, this research reveals that the performance of Islamic Bank’s fundraising before and during the Covid-19 pandemic is significantly different. This means that the Covid-19 pandemic has significant effect statistically on Bank Syariah Bukopin’ fundraising performance. The number of Bank Syariah Bukopin's third party Funds namely Wadiah Current Accounts, Wadiah Savings, Mudharabah Savings, and Time Deposits, has declined significantly during the covid 19 pandemic.